Determining a common understanding of interprofessional competencies for pre-registration health professionals in Aotearoa New Zealand: A Delphi study - Andersen, Patrea; Broman, Patrick; Tokolahi, Ema; Yap, Jia Rong; Brownie, Sharon (Frontiers in Medicine, 2023)
There is growing awareness that factors such as the growing incidence of co-morbidity and increasing complexity of patient health needs cannot be addressed by health professionals practicing in isolation. Given this, there is an increasing emphasis on preparing students in health-related programs for effective interprofessional practice. Less clear, however, are the specific skills and clinical or learning opportunities necessary for students to develop effectiveness in interprofessional practice. These factors drove a team associated with a tertiary health education provider in Hamilton, New Zealand to transform traditional clinical student experiences in the form of an interprofessional student-assisted clinic. The clinic was intended, in part, to provide students with opportunities to learn and experience interprofessionalism in practice but was hampered by limited information available regarding the specific skill requirements necessary for students in New Zealand to learn in this context. In this Delphi study, we synthesize national expert opinion on student competency indicators necessary for effective interprofessional practice. The resultant set of indicators is presented and opportunities for application and further research discussed. The paper offers guidance to others seeking to innovate health curricula, develop novel service-oriented learning experiences for students, and foster interprofessional practice competence in the future health workforce.